En torno a la muerte a finales de la Edad Media aragonesa. Around Death in the Kingdom of Aragon at the end of the Middle Ages - Falcón Pérez, María Isabel; García Herrero, María del Carmen (En la España Medieval, 2006)
This article tackles rituals and beliefs around death in the Kingdom of Aragon at the end of the Middle Ages. The presence of both the so-called macabre feeling and death and the afterlife are considered in Aragonese royal coronation parties. At the same time, it becomes clear that the Church had to deal with the fact that some people were agnostic and therefore rejected the idea of resurrection and afterlife. We inquire into diverse eschatological conceptions and consider testaments to focus our audience’s attention on some pious endowments that often have been overlooked: for example, the act of ordering chalices (an indicator of the rootedness and diffusion of the eucharistic cult), wax ex-votos (so scarcely documented) and the restauration of holy images located in temples.